Sensor‐Actuators: 4D Printing Strain Self‐Sensing and Temperature Self‐Sensing Integrated Sensor–Actuator with Bioinspired Gradient Gaps (Adv. Sci. 13/2020). Issue 13 (8th July 2020) - Chen, Daobing; Liu, Qingping; Han, Zhiwu; Zhang, Junqiu; Song, HongLie; Wang, Kejun; Song, Zhengyi; Wen, Shifeng; Zhou, Yan; Yan, Chunze; Shi, Yusheng
Abstract : In article number 2000584, Shifeng Wen, Yan Zhou, and co‐workers report a 4D printing strain self‐sensing and temperature self‐sensing integrated‐sensor–actuator with bio‐inspired gradient gaps. Using the 4D printing method, the bionic structure is creatively combined with smart materials to obtain the sensor–actuator components with self‐temperature sensing and active touching feedback properties, thus providing a promising approach to fabricate humanoid systems.